Density, viscosity, excess molar volume and viscosity deviation for [chloroform (1) + methanol (3)] binary system and [chloroform (1) + di-isopropylether (2) + methanol (3)] ternary system at 298.15 K - Medina Naessens, Ruth Natalia (2017)
Densities ρ and viscosity η of the [chloroform (1) + methanol(3)] binary system and [chloroform (1) + di-isopropyaelther (DIPE) (2) + methanol (3)] ternary system have been measured at 298.15 K and a pressure of 960 hPa using an Anton Paar DMA 500 stavigmeter. Excess molar volumes VE and viscosity deviation Δη were calculated. The excess molar volume and viscosity deviation for binary system were fitted to a Redlich-Kister type equation and the ternary excess molar volumes VE and viscosity deviation Δη were correlated by a Redlich-Kister and Nagata and Tamura type equation. Also, the ternary excess molar volume and viscosity deviation Y123 Ewere predicted using the Radojković equation. From the results we obtained conclusions about the molecular interactions in binary and ternary mixtures.